2022
DOI: 10.1088/1367-2630/ac45cd
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-driven wrinkling of soft inner-lined tubes

Abstract: A simple equation modelling an inextensible elastic lining of an inner-lined tube subject to an imposed pressure difference is derived from a consideration of the idealised elastic properties of the lining and the pressure and soft-substrate forces. Two cases are considered in detail, one with prominent wrinkling and a second one in which wrinkling is absent and only buckling remains. Bifurcation diagrams are computed via numerical continuation for both cases. Wrinkling, buckling, folding, and mixed-mode solut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Equations (2.1)–(2.3) become sn=pκtscriptFn,1emst=κnscriptFt,1emBsκ=n,where scriptFt and scriptFn are external axial and shear force per unit length, respectively. Recently, for instance, an analytically solvable model for elastic wrinkling on a nonlinear foundation was introduced, in which scriptFt=0 while scriptFn scales as some power of the local displacement of the elastica [26–28] (see also [2933] for more experimental and theoretical results on the subject).…”
Section: Generalization With Body Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Equations (2.1)–(2.3) become sn=pκtscriptFn,1emst=κnscriptFt,1emBsκ=n,where scriptFt and scriptFn are external axial and shear force per unit length, respectively. Recently, for instance, an analytically solvable model for elastic wrinkling on a nonlinear foundation was introduced, in which scriptFt=0 while scriptFn scales as some power of the local displacement of the elastica [26–28] (see also [2933] for more experimental and theoretical results on the subject).…”
Section: Generalization With Body Forcesmentioning
confidence: 99%
“…where F t and F n are external axial and shear force per unit length, respectively. Recently, for instance, an analytically solvable model for elastic wrinkling on a nonlinear foundation was introduced, in which F t = 0 while F n scales as some power of the local displacement of the elastica [26][27][28] (see also [29][30][31][32][33] for more experimental and theoretical results on the subject). We may continue to define H as Bκ 2 /2 + t. It now satisfies…”
Section: Generalization With Body Forcesmentioning
confidence: 99%
“…Recent work on a family of simple, yet realistic, models for substrate-supported elastic rings under compression [27] revealed that these models have a special structure that suggests that exact wrinkle solutions can be constructed, and that these may, in turn, be related to the well-known buckled states of the substrate-free case. In this Letter we show that this is indeed the case.…”
mentioning
confidence: 99%
“…In order to study the wrinkling of a thin elastic inextensible ring supported by a soft substrate, we consider the following model, which can be derived from the Kirchhoff equations for elastic rods [27,28]:…”
mentioning
confidence: 99%
See 1 more Smart Citation